Implications of Multimedia-based Differentiated Learning on TQM Learning at UHAMKA: Implikasi Pembelajaran Berdiferensiasi Berbasis Multimedia Pada Pembelajaran TQM di UHAMKA - Bunyamin, Bunyamin (Halaqa: Islamic Education Journal, 2023)
Education institutions have a challenge from societal changes, particularly when it comes to teachers and other educators. Teachers and lecturers must be innovative and inventive in their teaching methods due to the diverse learning styles of their students. Differentiated learning is one way to implement this learning. This study aims to implement differentiated learning in media-based Quality Control and Management (TQM) courses. Data were gathered through observation, interviews, and documentation during field study. According to this study, learning with Total Quality Management (TQM) differs from traditional learning in a few ways. Firstly, wordwall-based multimedia can be integrated seamlessly; secondly, learning was before purely passive but is now interactive thanks to multimedia-based.